In-service education in a neonatal unit of progressive care - Freitas, Nathalia Faria de; Cadete, Matilde Meire Miranda (Revista de Enfermagem UFPE on line, 2012)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> ABSTRACT Objective: to conduct focus groups with the nursing professionals in the neonatal unit. Method: it is a qualitative study, guided by the theoretical framework of the research-action, performed in the Neonatal Unit of Progressive Care, with nursing professionals who worked there for at least three months. Information was collected through participant observation, with registration in a field journal. Later, we constituted the study and discussion groups. The data were analyzed according to the Technique of Content Analysis, after the research project being approved by the Ethics Research Committee of the Santa Casa de Belo Horizonte, nº 011/2011. Results: the following categories have emerged: << Peripherally Inserted Central Catheter (PICC) >>, << Reality of the PICC at the unit >> and << Interventions to minimize the adverse events related to the PICC >>. Conclusion: the in-service education is an effective strategy in promoting the health of newborns at high risk and promoter of qualitative transformations for the integrality of the care. Descriptors: Health Education; Nursing; Catheter; Neonate. RESUMO Objetivo: realizar grupos de discussão com os profissionais de enfermagem na unidade neonatal. Método: estudo qualitativo, norteado pelo referencial teórico da pesquisa-ação, realizado na Unidade Neonatal de Cuidados Progressivos, com profissionais de enfermagem que lá atuavam há pelo menos três meses. As informações foram coletadas pela observação participante, com registro no diário de campo. Posteriormente, foram constituídos os grupos de estudos e de discussão. As informações foram analisadas de acordo com a Técnica da Análise de Conteúdo, depois de aprovado o projeto de pesquisa pelo Comitê de Ética da Santa Casa de Belo Horizonte, n. 011/2011. Resultados: emergiram as seguintes categorias: << Cateter central de inserção periférica (PICC)>>, << Realidade do PICC na unidade >> e << Intervenções para minimizar os eventos adversos relacionados ao PICC >>. Conclusão: a educação em serviço é estratégia efetiva na promoção da saúde dos recém-nascidos de alto risco e promotora de transformações qualitativas para a integralidade do cuidar. Descritores: Educação Em Saúde; Enfermagem; Cateter; Neonato. RESUMEN Objetivo: realizar grupos de enfoque con las profesionales de enfermaría en la unidad neonatal. Método: estudio cualitativo, orientado por la referencial teórica de la investigación-acción, llevada a cabo en la Unidad Neonatal de Cuidados Progresivos con los profesionales de enfermería que trabajaron durante al menos tres meses. La información se recolectó mediante la observación participante, con registro en el diario de campo. Posteriormente, se constituyeron los grupos de estudio y discusión. Las informaciones fueron analizados de acuerdo con la técnica de Análisis de Contenido, después de aprobado el proyecto de investigación por el Comité de Ética de la Santa Casa de Belo Horizonte, n. 011/2011. Resultados: surgieron las siguientes categorías: << El catéter central de inserción periférica (PICC) >>, << Realidad de PICC en la unidad >> y << Las intervenciones para minimizar los eventos adversos relacionados con PICC >>. Conclusión: La educación en servicio es una estrategia efectiva en la promoción de la salud de los recién nacidos de alto riesgo y promueve transformaciones cualitativas para la integralidad de la atención. Descriptores: Educación en Salud, Enfermería; Catéter; Neonato. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-fareast-font-family:Calibri; mso-bidi-font-family:"Times New Roman";} --> <!--[endif] -->